Status of Soil Physicochemical Properties in Forests and Savannas Restored Using the Ecosystem-Based Adaptation Approach in Eastern Rwanda - Venuste Nsengimana; Marguerite Mukangango; Jean de Dieu Habiyaremye; Fautine Uwiduhaye; Christella Suavis Iradukunda; Yvonne Bigengimana; Florien Nsanganwimana (Applied and Environmental Soil Science)
The concept of soil quality was developed to describe the capacity of soil to perform ecosystem functions properly. Nowadays, soil quality is affected by climate change effects. To remediate the problem, the ecosystem-based adaptation approach (EbA) was initiated to restore degraded ecosystems. In Rwanda, the approach was initiated in 2016 to restore degraded wetlands, savannas, and forests. However, nothing is known about how the restoration improved soil quality. This research aims to reveal the status of soil physicochemical properties in restored forests and savannas in Eastern Rwanda. Soil cores were collected and analyzed for soil pH, electrical conductivity, ammonium, nitrates, total nitrogen, organic carbon, available phosphorus, calcium, magnesium, potassium, sodium, cation exchange capacity, structure, texture, and soil water content. Results indicated that the restored and natural forests offer better conditions of soil properties. The restored forest (plot A) had lower level of soil pH and had higher electrical conductivity, total nitrogen, organic carbon, available phosphorus, calcium, potassium, magnesium, cation exchange capacity, and sandy loam soil type. The nonrestored forest (plot B) was rich in ammonium, silt, water content, and sandy loam soil type, while the natural forest (plot C) was rich in soil pH, electrical conductivity, total nitrogen, organic carbon, calcium, magnesium, cation exchange capacity, and soil water content and had loam soil compared to plots A and B. In savannas, all plots were similar in vegetation type and tree species. Higher levels of ammonium were found in plots A and C. The available phosphorus and potassium content was significantly higher in plot A than in the plots B and C. In all savanna plots, soil was sandy loam. Like in the forests, sodium was the same in all plots. We recommend future studies to validate these findings.